FINANCING TOOLS FOR "GREEN" INVESTMENT IN THE CONDITIONS OF SUSTAINABLE DEVELOPMENT (Development Service Industry Management, 2024)
This article presents a novel theoretical and methodological study of the existing financing tools for 'green' investment, determining their effectiveness and developing recommendations for improving the mechanisms of financing environmentally oriented projects in the conditions of sustainable development. The article delves into modern approaches and tools for financing projects to preserve the environment and ensure sustainable development. The main mechanisms of attracting funds for environmentally friendly technologies, renewable energy, waste management, and other initiatives that reduce the negative environmental impact are analyzed.The tools for financing "green" projects were considered, and it was determined that one of the most popular tools is "green" bonds, which attract capital from institutional and private investors to implement projects that meet environmental standards. The current state of the "green" bond market has been analyzed, and the main trends and prospects for its development have been determined. In addition to green bonds, other financial instruments are being considered, such as environmental loans, specialized investment funds, grants and subsidies, and public-private partnership mechanisms. Special attention is paid to international financial institutions, such as the World Bank, the International Monetary Fund, and the European Bank for Reconstruction and Development, which provide financial support for implementing sustainable development projects. The impact of regulatory policy and government initiatives on stimulating "green" investment is also considered.The importance of integrating environmental criteria into the investment decision-making process and the need for infrastructure development to support 'green' investments have been determined. The article offers practical recommendations for improving financial instruments and mechanisms that can contribute to the more active involvement of private capital in environmental projects. It was concluded that the effective use of financial instruments can significantly accelerate the transition to an environmentally sustainable economy, providing tangible benefits for both the environment and the economy.
Keywords: sustainable development; financing tools